Hydrogen production and hydrogen utilization in the rumen: key to mitigating enteric methane production - Roderick I. Mackie; Hyewon Kim; Na Kyung Kim; Isaac Cann (Animal Bioscience, 2024)
Molecular hydrogen (H2) and formate (HCOO−) are metabolic end products of many primary fermenters in the rumen ecosystem. Both play a vital role in fermentation where they are electron sinks for individual microbes in an anaerobic environment that lacks external electron acceptors. If H2 and/or formate accumulate within the rumen, the ability of primary fermenters to regenerate electron carriers may be inhibited and microbial metabolism and growth disrupted. Consequently, H2- and/or formate-consuming microbes such as methanogens and possibly homoacetogens play a key role in maintaining the metabolic efficiency of primary fermenters. There is increasing interest in identifying approaches to manipulate the rumen ecosystem for the benefit of the host and the environment. As H2 and formate are important mediators of interspecies interactions, an understanding of their production and utilization could be a significant starting point for the development of successful interventions aimed at redirecting electron flow and reducing methane emissions. We conclude by discussing in brief ruminant methane mitigation approaches as a model to help understand the fate of H2 and formate in the rumen ecosystem.